PDE: possibilidades e limites da formação teórico-metodológica dos professores de matemática do NRE/FB (2007-2013) - Nesi, Elisângela Rovaris (2015)
Inserted in the research line of Society, Knowledge and Education of the Master degree in Education of UNIOESTE - Francisco Beltrão, the research has as its object the training of mathematics teachers in Paraná Educational Development Program - PDE, from 2007 to 2013, linked to Regional Education Center of Francisco Beltrão - PR. In the face of hegemonic tendency of teacher training that emphasizes the formal and practical aspects rather than on theoretical training of teachers, the research seeks to answer the following issues: to what extent has the PDE provided a theoretical and methodological training? If so, in which perspective? The goal is to analyze in which level the PDE has enabled a theoretical and methodological training to the math teacher from the perspective of mathematics education established in the Curriculum Guidelines of Paraná. It aimed, specifically, through research: a) identify the actions taken by the PDE program related to the changes in the continuing training of teachers; b) understand the educational guidelines and routing of PDE / PR as a public policy of continuing training and the changes pointed by mathematics teachers; c) analyze the materials produced by PDE teachers: intervention projects, proposal of the pedagogical implementation and the scientific article, considering the proposal of the Curriculum Guidelines and mathematics education. The methodology used in this research is literature with content analysis, prescribing guidelines from Gil (2002) and Bardin (1977). The research is organized into three parts: the first part presents a discussion of the different educational movements of teacher training: the financial capital project that meets the dominant interests and the critical movements which implies the fight of education professionals for quality training that values the individuals and their interactions with the environment. The second part presents the proposal of a theoretical and methodological training of teachers in mathematics and its relations with scientific knowledge, the theoretical and didactic concepts covered in the Curriculum Guidelines focused on mathematics education and the relationships established throughout the Continued Training Program - PDE. An online questionnaire was used. It had open and closed questions which were sent to teachers by Google docs. The third part is made up of the analysis of the scientific production of PDE teachers and of research issue. The results show that the PDE enables conditions of changes in the theoretical and methodological training of participating teachers concerning the available time to study outside the classroom, return to university space with a guiding teacher of the IES for scientific production, the possibility of contact with other educators and their realities, by specific courses on this school subject and the ones related to the education field and financial aid for spending on training. Analysis of the material produced by the PDE's teachers shows that there are difficulties in articulating the proposed curriculum in mathematics education with the mathematical knowledge and pedagogical knowledge. Only two of the professionals in this research have achieved the theoretical and methodological development in mathematics, relating the DCE's with the teaching of mathematics through the PDE.